Effect of Am addition on oxygen potential in (U0.55Pu0.3Am0.15)O2−x - Keisuke Yokoyama; Masashi Watanabe; Akane Usui; Takayuki Seki; Takashi Onishi; Masato Kato (Nuclear Materials and Energy)
Oxygen potential measurement was conducted at 1273 K, 1473 K, 1573 K, and 1623 K for (U0.55Pu0.3Am0.15)O2−x using a thermogravimeter and oxygen sensors. Adding 15% Am instead of U increased the oxygen potential of (U0.7Pu0.3)O2−x by 100 – 150 kJ/mol. The measured oxygen potentials were analyzed by the defect chemistry method. This analysis showed that the oxygen potential of (U0.55Pu0.3Am0.15)O2−x was formulated as a function of O/M ratio and temperature, and that the calculated results were consistent with the measured data. The cation valence is estimated to be (U4+0.4U5+0.15Pu4+0.3Am3+0.15)O2.00 in the stoichiometric composition.